1999
DOI: 10.1212/wnl.53.9.2176
|View full text |Cite
|
Sign up to set email alerts
|

Intracerebral hemorrhage outcome: Apolipoprotein E genotype, hematoma, and edema volumes

Abstract: We investigated whether early hematoma or edema volumes could explain the adverse association between APOE epsilon4 and survival in intracerebral hemorrhage. Among 102 patients, epsilon4 carriers had a higher mortality rate than non-epsilon4 carriers (38 versus 24%, p = 0.05). Nonsurvivors had larger hematoma (75.5 cm3 versus 27.1 cm3, p<0.001) and edema volumes (37.5 cm3 versus 17.1 cm3, p<0.01), but these were not associated with epsilon4 after adjusting for race, age, and type of hemorrhage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 9 publications
2
52
2
Order By: Relevance
“…Mean GCS was 8 (range [3][4][5][6][7][8][9][10][11][12][13][14][15] In our series we found GCS range 3-15, our findings were compared with the findings of other studies demonstrated in tabulated form below:…”
Section: Resultssupporting
confidence: 57%
“…Mean GCS was 8 (range [3][4][5][6][7][8][9][10][11][12][13][14][15] In our series we found GCS range 3-15, our findings were compared with the findings of other studies demonstrated in tabulated form below:…”
Section: Resultssupporting
confidence: 57%
“…The Δ4 allele is catabolized three times faster than the Δ2 allele in heterozygous Δ2/Δ4 subjects, suggesting that these alleles may have distinct metabolic pathways [9, 10]. Given differential metabolisms, the assorted alleles also have diverse effects on neuronal plasticity and survival [10, 11, 17, 18, 19, 20, 21, 22, 23]. The Δ3 allele has been shown to support the effective repair and remodelling after injury by noxious agents in a dose-dependent fashion.…”
Section: Gene Variantsmentioning
confidence: 99%
“…The APO E genetic polymorphism has been shown to modify the risk for a variety of diseases, including breast cancer [1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55]. We refer the reader to important reviews by Mahley and Rall [1]and Smith [23], who provide detailed discussions of APO E on the risk of common human diseases and on ageing.…”
Section: Cellular Repair and Protective Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have highlighted the critical role of apoE in brain plasticity after injury (in vivo and in vitro models) [6][7][8][9][10]. On the other hand, to date, few studies have addressed the importance of apoE during early postnatal development, although apoE mRNA has been shown to increase at birth, during suckling, and after fasting in the rat liver [11].…”
Section: Introductionmentioning
confidence: 99%